Pregnancy and Pandemic - Schachner, Casey (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
In this article, I examine through personal narrative my experience as a sculptor, arts educator, and pregnant woman during the COVID-19 crisis paired with comparable stories and anecdotes collected from other pregnant women’s experiences during the pandemic. I hope to explore the effects—social, mental, and career related—of being at different stages of pregnancy during this international crisis. Working in a collaborative environment, such as an art studio, I have gained tremendous support over the years from fellow women, some of whom are also mothers, on how to navigate the ins and outs of working in fine arts academia. Now with the current pandemic underway, these resources are still present yet distant, as they virtually manage and maintain their own family units and careers. The 2019-2020 academic year was also my first year in a tenure-track faculty role. I am curious about the effects of COVID-19 and the additional effects of being pregnant in a pandemic. What toll will this crisis take on my career as a young female educator and on my perspective as a new mother? I have gathered information from other pregnant women who are experiencing pregnancy during this crisis and have included their statements in this article. I am interested in perspectives of women both in arts-related careers and outside of the arts as well. Although my voice and experience may be the dominant thread throughout the writing, the unifying theme will be of the resilience of the female mind and body, especially during these dynamic and precarious times of pregnancy and pandemic.